Hadith #645 - Sahih Muslim - Jubayr bin Mut'im (Sahih Muslim)
The people contended amongst themselves in the presence of the Messenger of Allah (ﷺ) with regard to bathing. Some of them said: We wash our heads like this and this. Upon this the Messenger (ﷺ) said: As for me I pour three handfuls of water upon my head.
Grade: Sahih

Hadith #646 - Sahih Muslim - Jubayr bin Mut'im (Sahih Muslim)
I pour water over my head thrice.
Grade: Sahih

Hadith #937 - Sahih Muslim - Jubayr bin Mut'im (Sahih Muslim)
I heard the Messenger of Allah (ﷺ) reciting Surat al-Tur (Mountain) (lii) in the evening prayer.
Grade: Sahih

Hadith #2839 - Sahih Muslim - Jubayr bin Mut'im (Sahih Muslim)
I lost my camel and went in search of it on the day of ‘Arafa, and I saw the Messenger of Allah (ﷺ) staying along with people in ‘Ara’fit. Thereupon I said: By Allah, he is among the Hums (Quraish) ; what has happened to him that he has come to this (place)? The Quraish were counted among Hums.
Grade: Sahih

Hadith #5949 - Sahih Muslim - Jubayr bin Mut'im (Sahih Muslim)
I am Muhammad and I am Ahmad, and I am al-Mahi (the obliterator) by whom unbelief would be obliterated, and I am Hashir (the gatherer) at whose feet mankind will be gathered, and I am ‘Aqib (the last to come) after whom there will be no Prophet.
Grade: Sahih

Hadith #5950 - Sahih Muslim - Jubayr bin Mut'im (Sahih Muslim)
I have many names: I am Muhammad, I am Ahmad, I am al-Mahi through whom Allah obliterates unbelief, and I am Hashir (the gatherer) at whose feet people will be gathered, and I am ‘Aqib (after whom there would be none), and Allah has named him as compassionate and merciful.
Grade: Sahih

Hadith #6306 - Sahih Muslim - Jubayr bin Mut'im (Sahih Muslim)
There is no alliance (hilf) in Islam but (the hilf) established in the pre-Islamic days (for good). Islam intensifies and strengthens it.
Grade: Sahih

Hadith #6360 - Sahih Muslim - Jubayr bin Mut'im (Sahih Muslim)
The severer would not enter Paradise. Ibn Umar said that Sufyan (explained it as): One who severs the tie of kinship would not enter Paradise.
Grade: Sahih